The Quality of Public Services in the Rancaekek Kencana Urban Village in Bandung District - Ai Nunung (Syntax Corporation Indonesia, 2020)
Realizing the quality of public services in order to support government administration in which there must be responsive to be able to provide services quickly, namely in the completion of administrative management in accordance with predetermined operational standards and precisely where the accuracy in terms of clarity of information regarding administrative completeness must be known. The purpose of this study is to find out how the quality of public services in Rancaekek Kencana urban village in Bandung district. This type of research is a descriptive study with a qualitative approach. Data analysis technique used is a model of data analysis techniques (Miles & Huberman, 1992) in (Sugiyono, 2017) namely data reduction, data display and conclusion drawing / verification. Based on the research results obtained that can be seen not said to provide a maximum service related to the process of public service activities to the community, especially in the process of administering administrative files such as handling a family card recommendation letter (KK) where there is not yet a maximum reflection of service from the apparatus the government as a provider of public services in terms of responsiveness, reliability, guarantee, empathy, and tangible in terms of supporting services to the community. Therefore the researcher concludes that the village government office should be able to provide services quickly, carefulness in providing services must be more careful and must evaluate the services provided in terms of facilities and infrastructure Keyword: quality of public service, urban village